Scientific and pedagogical activity of V. G. Bazhaiev at the Kyiv Commercial Institute - I. A. Sichenko (History of science and technology, 2016)
By means of methods of the historical and scientific, historical and comparative, bibliographic, source study and archival analysis is lighted up role of the well-known scientist-economist and the teacher, professor V. G. Bazhaiev in activity of the Kyiv commercial institute (nowadays – the Kyiv national economic university of Vadym Hetman). The role of V. G. Bazhaiev is certain in the development of commercial and economic education in Ukraine at the beginning of the XX-th century. The basic works of scientist this period are analyzed.